How Product-Plot Integration and Cognitive Load Affect Brand Attitude: A Replication. Issue 1 (2nd January 2016) - Pantoja, Felipe; Rossi, Patricia; Borges, Adilson
Abstract : Marketers are progressively using product placements to counteract technology that enables consumers to skip advertisements. However, consumers are increasingly multitasking while they watch videos, which might affect placement effectiveness. In France we conceptually replicate research on product–plot integration and multitasking that was originally conducted in the United States to analyze how different levels of cognitive charge influence this phenomenon. Results show that participants under moderate cognitive load liked intrusive placements. However, participants under high cognitive load were significantly less positive toward intrusive placements. The results show a potential U-shaped relationship between placement integration and levels of cognitive load.